Perceptions from people with physical disabilities about accessibility and social conditions: interventions for rehabilitation nursing - Rute Salomé da Silva Pereira; Salomé Sobral Sousa; Maria Manuela Martins; Wiliam César Alves Machado; Soraia Dornelles Schoeller (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to analyze the experiences of people with acquired physical disabilities regarding accessibility and social conditions; to identify nurse-led rehabilitation interventions for accessibility and social conditions; to determine nursing-sensitive indicators to improve accessibility and social conditions. Methods: a descriptive-exploratory qualitative study employed semi-structured interviews with people with acquired physical disabilities through purposive snowball sampling to address all objectives. Data analysis followed Bardin’s content analysis principles. Furthermore, objectives 2 and 3 were achieved through a reflective theoretical approach. Results: the 27 participants reported accessibility challenges, impacting activities of living and social conditions. This influences rehabilitation nursing, leading to three intervention fields: Assess the ability to perform activities of living and influencing factors; Develop and implement training to perform activities of living; Promote mobility, accessibility, and social participation. Final Considerations: based on participants experiences, we identified nurse-led rehabilitation interventions to promote accessibility and social conditions.